2008
DOI: 10.3141/2061-07
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Road Crash Frequency with Spatial Models

Abstract: Despite the evident spatial character of road crashes, limited research has been conducted in road safety analysis to account for spatial correlation; further, the practical consequences of this omission are largely unknown. The purpose of this research is to explore the effect of spatial correlation in models of road crash frequency at the segment level. Different segment neighboring structures are tested to establish the most appropriate one in the context of modeling crash frequency in road networks. A full… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
118
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 205 publications
(130 citation statements)
references
References 34 publications
10
118
2
Order By: Relevance
“…The elasticity of AADT appears a little high in this study compared with some of the previous studies which reported that the elasticity ranges from 0.6 -0.7 (e.g. Abdel-Aty and Radwan, 2000; Bird and Hashim, 2006;Aguero-Valverde and Jovanis, 2008). This may be because these studies were undertaken under different road conditions.…”
Section: Aadt and Road Segment Lengthcontrasting
confidence: 52%
See 4 more Smart Citations
“…The elasticity of AADT appears a little high in this study compared with some of the previous studies which reported that the elasticity ranges from 0.6 -0.7 (e.g. Abdel-Aty and Radwan, 2000; Bird and Hashim, 2006;Aguero-Valverde and Jovanis, 2008). This may be because these studies were undertaken under different road conditions.…”
Section: Aadt and Road Segment Lengthcontrasting
confidence: 52%
“…The Poisson based models include the Poisson-lognormal model (e.g. Lord and Miranda-Moreno, 2007;Aguero-Valverde and Jovanis, 2008); and the Poisson-gamma model (also known as Negative Binomial model) which is widely used in accident analysis (e.g. Shankar et al, 1995;Milton and Mannering, 1998;Abdel-Aty and Radwan, 2000;Lord, 2000;Amoros et al, 2003;Noland and Quddus, 2004;Kim et al, 2006;Haynes et al, 2007).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations